2011
DOI: 10.1111/j.1440-1819.2010.02167.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypomanic episodes during menstrual periods: Bipolar II disorder?

Abstract: O UR PATIENT, A 40-year-old woman with bipolar disorder, was admitted to our unit complaining of dizziness and diplopia for the last 2 days. The patient had been undergoing stable carbamazepine (CBZ) treatment (600 mg/day) for 10 years. CBZ levels were regularly measured and they were within therapeutic range (7.3 mg/mL, 16 days before admission). Four days before the patient's admission she was prescribed fluconazole (150 mg/day) for a fungal cervical infection. After 2 days of antimycotic treatment, the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 6 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…Several case studies document menstrual fluctuations in symptoms of bipolar disorder. All but one study 43 identified in the present review reported instances of hypomania, 47 mania, 41 or psychosis 50 during the premenstrual and menstrual phases. Kukopoulos and colleagues 40 reported that a 28-year-old Sardinian woman regularly experienced hypomania two weeks and depression two days prior to menstruation, with gradual improvement throughout menstruation.…”
Section: Resultsmentioning
confidence: 78%
“…Several case studies document menstrual fluctuations in symptoms of bipolar disorder. All but one study 43 identified in the present review reported instances of hypomania, 47 mania, 41 or psychosis 50 during the premenstrual and menstrual phases. Kukopoulos and colleagues 40 reported that a 28-year-old Sardinian woman regularly experienced hypomania two weeks and depression two days prior to menstruation, with gradual improvement throughout menstruation.…”
Section: Resultsmentioning
confidence: 78%
“…This vulnerability or hormonal priming may be genetic, a result of the organizational effects of hormones, or both, among other things. For instance, two case reports reviewed herein suggested that BD developed right after menarche and, according to Labad et al. , the onset of BD tends to be closer to menarche than that of unipolar depression.…”
Section: Discussionmentioning
confidence: 77%
“…There are approximately three times more published cases of hypomania or mania than bipolar depression or dysphoria entrained to, or exacerbated in, the premenstrual phase. In fact, 10 reports of exclusively hypomania and mania in the premenstrual phase have been published in the last 19 years . Interestingly, Al‐Habeeb outlined diagnostic research criteria for premenstrual mania disorder (PMMD) as well as a case study.…”
Section: Resultsmentioning
confidence: 99%
“…The authors have postulated this to be a case of bipolar-II disorder (8). Repeated pre-menstrual manic episodes have been reported as an unusual manifestation of premenstrual syndrome (8). In contrast, other studies have reported a lack of relationship between bipolar disorder and menstruation (10).…”
Section: Discussionmentioning
confidence: 89%
“…There is a similar case report of a patient with recurrent menstrual hypomanic episodes without a history of depression. The authors have postulated this to be a case of bipolar-II disorder (8). Repeated pre-menstrual manic episodes have been reported as an unusual manifestation of premenstrual syndrome (8).…”
Section: Discussionmentioning
confidence: 89%